Os três momentos pedagógicos e a interdisciplinaridade no ensino de ciências da natureza - Crestani, Eva Rita Machado Ferreira (2018)
The current reality in our schools highlights the need for interrelated teaching, teaching that helps the student, beyond the construction of knowledge, the broader understanding of the world in which he lives. The present work, linked to the line of research: Theoreticalmethodological Foundations for Science and MathemaTICs Teaching sought to develop an Educational Product (PE) with the intention of contributing to the promotion of such teaching. For that, a Teaching Sequence (SD) based on the Three Pedagogical Moments (3MP) dynamics was elaborated by the professors of Chemistry, Physics and Biology and in an interdisciplinary perspective, the way in which the knowledge of Chemistry, Physics and Biology inter -related. The EP, titled “Our daily heat”, was applied in a class of the second serie of Normal Course, Medium Level, in a public school in the municipality of Santa Rosa -RS. The data were obtained through the meetings held with theteachers participating in the research, as well as the classes applied with the students through a Logbook (DB) where each teacher recorded their observations and reflections during the course development; this dissertation accompanies the educational product, which is available athttp://educapes.capes.gov.br/handle/capes/207043.